INTEGRATED GIS AND SATELLITE REMOTE SENSING IN MAPPING THE GROWTH, MANAGING AND PRODUCTION OF INLAND WATER FISHERIES AND AQUACULTURE - Al-Mahdi, Ambare Muhammed; M.S. Ndahi, Ezekiel; Yahaya, Babagana; Lawan Maina, Muhammed (European Scientific Journal, ESJ, 2014)
Geographic Information System (GIS) Technology is becoming an essential tool for combining various map and satellite information sources in models that simulate the interactions of complex natural systems. With the help of GIS, management of incredible quantity of data such as traditional digital maps, database, models etc., is now possible. Remote sensing provides the most important informative contribution to GIS which furnishes basic informative layers in optimal time and space resolutions (Sivakumar and Donald, 2011).